Thermistor formation using batio3 powders synthesised by the pechini method (2010)
Barium titanate (BaTiO3) is a compound of interest in the field of electroceramics which is widely used in the manufacture of capacitors, piezoelectric transducers and resistive devices having a positive temperature coefficient (PTCR) and in manu- facturing pyroelectric and optoelectronic devices. Most of these devices are obtained by consolidating high purity, suitable sized particle ceramic powders; structured synthesis methods are required to ensure such requirements. BaTiO3 powders were synthesised by a polymeric precursor method (Pechini) in this work. Very pure, small particle sized, raw material was obtained. These powders were characterised using thermo- gravimetric and differential thermal analysis (TGDT), X-ray diffraction (XRD) and differential scanning calorimetry (DSC). The results indicated that samples treated at 650°C presented cubic BaTiO3 as unique crystalline phase. If a sample were treated at 1,100°C, the tetragonal phase having a c/a